PENGEMBANGAN KARTU TANDA MAHASISWA UNIVERSITAS GADJAH MADA MENJADI SISTEM TIKET ELEKTRONIK MODA ANGKUTAN UMUM TRANS JOGJA - Munawar, Ahmad; Angelina, Synthia (Jurnal Transportasi, 2012)
The use of smart cards and supporting devices to support the reform of urban public transportation does not stop at the ticket machine alone, as it has been successfully developed for the bus transit system Trans Jogja. The development is also aimed for the use of Prambanan Express train and Trans Batik Solo bus services, resulting in the integration of the three modes using a single smart card ticket. The smart card system needs to be improved so that the Student Identity Card of Gadjah Mada University is accepted and can be used as a smart card for the bus and train services. For short-term period, this study aimed to estimate the number of students who will use the Student Identity Card to buy Trans Jogja bus tickets, while for long-term period the results of this study can be used to provide direction for the development of Trans Jogja bus routes in the future. Survey was conducted through interviews with 500 students of Gadjah Mada University. The results indicate that there is a significant number of students who will use the bus service of Trans Jogja system, amounting to 890 people. For long-term period, the results suggest that the bus route development, based on the potential demand, should reach the north area of the Gadjah Mada University campus.Keywords: smart cards, urban public transport, bus tickets